Better accuracy of robotic-assisted total knee arthroplasty compared to conventional technique in patients with failed high tibial osteotomy - Baek, Ji-Hoon; Lee, Su Chan; Lee, Dong Nyoung; Heo, Juneyoung; Kim, Taehyeon; Ahn, Hye Sun; Nam, Chang Hyun (PLOS ONE, 2024)
Purpose This study aimed to compare the clinical outcomes, mechanical axis, component positioning, leg length discrepancy (LLD), and polyethylene liner thickness between robotic-assisted total knee arthroplasty (TKA) and conventional TKA in patients with failed high tibial osteotomy (HTO). Methods A total of 30 patients (30 knees) with failed HTO who underwent TKA using a robot-assisted system between June 2020 and December 2023 were included in this study (robotic group). Additionally, 60 patients (60 knees) with failed HTO who underwent conventional TKA were included as controls (conventional group). Propensity score matching was performed using a 2:1 ratio between the matched participants. The mean follow-up period was 2.1 years in the robotic group and 2.2 years in the conventional group. Clinical evaluations were performed using the Knee Society Score (KSS) rating system. Mechanical axis, component coronal and sagittal positioning, and LLD were evaluated using postoperative radiographs. The thickness of the polyethylene liner was also determined. The mean error values and outliers were calculated and compared between the two groups to determine the accuracy of the mechanical axis, postoperative component positioning, and LLD. Results The postoperative KSSs in the robotic and conventional groups were not statistically different. The robotic group achieved better accuracy than the conventional group in terms of postoperative mean mechanical axis (1.7° vs. 2.4°, p < 0.05), femur coronal inclination (90.0° vs. 91.6°, p < 0.05), tibial coronal inclination (90.3° vs. 91.3°, p < 0.05), tibial sagittal inclination (90.5° vs. 91.4°, p < 0.05), and LLD (2.2 vs. 7.0 mm, p < 0.05). A significant difference in polyethylene liner thickness was observed between the two groups (p < 0.05). Conclusions Robotic-assisted TKA showed improved mechanical axis, higher accuracy of component positioning and polyethylene liner thickness, and reduced LLD compared with those of conventional TKA in patients with failed HTO. Further studies with a larger sample size and long-term follow-up are warranted to ascertain whether the accuracy of robotic-assisted TKA can translate into better clinical outcomes and patient satisfaction.